The Effectiveness of Project-Based Learning Model on Students’ Narrative Writing Skills at SMA Jayanegara - jafar Jafar (Cita konsultindo, 2026)
Narrative writing is an essential component of language learning that requires students to generate ideas, organize them coherently, and express them using appropriate language features. However, students’ narrative writing skills are often underdeveloped due to the dominance of teacher-centered instructional practices. This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model in enhancing students’ narrative writing skills at SMA Jayanegara. This research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The participants consisted of 28 students. Data were collected through narrative writing tests administered before and after the implementation of the PjBL model. The data were analyzed using descriptive statistics, normality tests, paired sample t-test, and N-Gain analysis. The results revealed a significant improvement in students’ narrative writing skills. The mean score increased from 65.25 in the pretest to 87.50 in the posttest. The paired sample t-test showed a statistically significant difference (p < 0.05), indicating the effectiveness of the intervention. Furthermore, the N-Gain value of 0.64 was categorized as moderate, suggesting a meaningful level of improvement. These findings indicate that the implementation of the Project-Based Learning model effectively enhances students’ narrative writing skills by promoting active engagement, collaboration, and reflective learning. Therefore, PjBL can be considered a suitable instructional approach for improving writing skills in Indonesian language education.